An automation framework design for secure software development. Issue 10 (31st July 2019) - Mythily, M.; Valarmathi, M.L.; Anand Deva Durai, C.; Rexie, J.A.M.
Abstract: Business process modeling (BPM) is procedural‐oriented advanced activity for representing process models with domain knowledge. It consists of all the functional requirements given by the users to build the software. However, nonfunctional requirements such as cost, time, performance, and security are used to evaluate the performance of a system. Among these requirements, security is the vital attribute to be taken care at the early stage of any software development. For example, even governing bodies are heavily dependents on the data system due to security exposures. So automation on model transformation from non‐secured metamodel to secured metamodels improves the overall execution of the software evolution process. In this paper, the authors propose an Auto Secure Business Process (AutoSBP) system to automate security to the existing software models. The activity model of existing system is dismantled into attributes and actions to extract its business need. Based on the interpretation from business data, security implications are applied to the existing software models. To fine tune the security implications, ID3 decision learning algorithm is applied. The effect of the system‐generated model assures the quality by its complexity metrics. Abstract : To achieve model transformation to save effort and reduce errors by automating the building and modification of models. To update an existing software into security requirement incorporated software in order to enhance the security perspective of the software. To optimize the security of the software with respect to the domain aspects since each business has different priority on their data.